STUDENT’S SOCIAL STATUS AS A FACTOR OF ASSESSMENT OF THE UNIVERSITY’S ORGANIZATIONAL CULTURE - Kalenchuk, Valentyna Oleksandrivna (Insight: the psychological dimensions of society, 2019)
The transition to the new educational paradigm requires higher flexibility and variability from higher education. Transformations should also occur in the field of interpersonal communication, covering all participants in the educational process. Therefore, we consider it appropriate to appeal to the analysis of the phenomenon of the organizational culture. The purpose of the research is to clarify the attitude of student youth to the organizational culture of the university depending on the social status of the student in group interaction. The following methods have been applied for the research: “The scale of organizational paradigms” (L. Konstantin); J. Moreno’s method of sociometric measurements, carried out according to the parametric criteria, that is, with a limited number of choices. Sociometry has been applied to identify the status of students in group communication. Results. Based on the analysis of ideas about the real and desirable images of the organizational culture of the higher education institutions, it has been found that the organizational culture of the university corresponds to a hierarchical, bureaucratic model; the desirable image of the organizational culture corresponds to a democratic, general model, where the educational process is characterized by a high level of coherence of interaction. The differences between students with high and low status in the level of satisfaction with the real situation of the organizational culture of the university have been determined, the students with a higher status get certain pleasure from their official activities, however, they are less interested in maintaining emotional relations with students in the group, in obtaining approval from them. The students with a higher formal status, are capable of active behavior, of taking the initiative, are characterized by critical thinking, the tendency to analyze the situation that develops, the desire for leadership, the desire to take responsibility, therefore, for many parameters of the organizational culture their assessments are lower. Conclusions. It has been proved that there are differences of the real and desirable student youth’s assessment of the organizational culture, the real culture is perceived as more closed, the desirable culture is more open and democratic.